Columns Cross-Section Shape Effect on Punching Shear in Reinforced Concrete Flat Slabs - Mohammed Oleiwi (Journal of Techniques)
Punching shear is one of the possible failures that must be taken into consideration in designing concrete slabs and foundations. Several factors control the occurrence of this failure mechanism, such as slab thickness, concentrated loads, and the cross-section area of the supporting columns. The cross-section shape of columns may also affect the punching shear in flat slabs. Therefore, this research was specified to study the effect of the columns' cross-section shape on the punching shear in flat slabs by conducting a simulation analysis for two multi-story concrete buildings with a flat slab but with different structural stability systems, building layout, and column distribution, where five cross-section shapes (square, rectangular, circular, hexagonal, and octagonal) were tested. ETABS 2016 software was adopted for modeling and analysis to identify the optimum column shape leading to minimizing punching shear. Although the cross-section area and the reinforcement area of the columns were fixed while changing the models’ column shapes, it was found, in both buildings, that hexagonal columns performed better than others under punching shear and provided the lowest punching shear ratio. In contrast, circular columns gave the lowest resistance. Octagonal, square, and rectangular columns, respectively, follow the hexagonal columns in resisting punching shear.